BGT404 – Horticultural Science (Sains Hortikultur) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK (Universiti Sains Malaysia, 2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 BGT404 – Horticultural Science (Sains Hortikultur) Duration: 2 hours (Masa: 2 jam)